1998
DOI: 10.1046/j.1360-0443.1998.9322317.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between work stress, alcohol consumption and sickness absence

Abstract: The association between abstinence and sickness absence could reflect medical problems of abstainers or a lack of skills for coping with stress. The failure to find a significant detrimental effect of excessive drinking may have been due to use of a low threshold for excessive drinking and/or low power. Prospective studies are needed to gain insight in causal relationships between the variables concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 2 publications
5
76
1
5
Order By: Relevance
“…15 Men may react to stress by increasing alcohol use. 29 The present study showed that eating behaviors of workers having 'Tension/Anxiety' under job stress resembled those of obese persons. The category related to obesity such as 'Eating style,' 'Feeling of satiety,' 'Cognition of constitution,' 'Motivation for eating' suggest that workers feeling stressed are prone to eat much.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…15 Men may react to stress by increasing alcohol use. 29 The present study showed that eating behaviors of workers having 'Tension/Anxiety' under job stress resembled those of obese persons. The category related to obesity such as 'Eating style,' 'Feeling of satiety,' 'Cognition of constitution,' 'Motivation for eating' suggest that workers feeling stressed are prone to eat much.…”
Section: Discussionmentioning
confidence: 78%
“…21,22 This questionnaire is used Obesity and job stress in male Japanese workers N Nishitani and H Sakakibara in some hospitals for obesity treatment in Japan. 23 These 30 questions are classified into the seven areas regarding cognition of constitution (1-3), eating style (4-6), eating rhythm abnormalities (7,8,16,17,30), feeling of satiety (9,10,24,25,28), substitute eating and drinking (11,18,19,(21)(22)(23), meal contents (12)(13)(14)(15)20), and motivation for eating (26,27,29).…”
Section: Study Subjectsmentioning
confidence: 99%
“…Some studies have found that this imbalance increases the risk for alcohol dependence among men 8) , but others have found no significant correlation with heavy drinking 1) . Drinking is also reported to be influenced by social support 19) . Workplace support can be divided into general support and support that directly relates to drinking, and both types of support may play a role in drinking among workers 32) .…”
Section: Introductionmentioning
confidence: 99%
“…A nivel laboral generan un incremento importante de los riesgos inherentes al trabajo (Zwerling y cols; 1990) (Alleyne, BC; Stuart, P; Copes, R; 1991) (Cabrero, E; Osuna, E; Luna, JD; Jiménez-Bueno, MC; Blanco, A; Luna, A; 1996) (Cabrero, E; Osuna, E; Luna, JD, Jiménez, MC; Blanco, A; Luna, A; 1996) (Blum, TC;Roman, PM;Martín, JK; (Aurrekoetxea, J;Echenagusia, VM; (Vasse, RM;Nijhuis, FJN;Kok, G;, por lo que deberían adoptarse medidas para diagnosticar, tratar y reinsertar a los trabajadores afectados por las drogodependencias y cualquier programa preventivo o asistencial que se realice en el medio laboral debería ser apoyado toda la sociedad, empresariado y Administración (Cabrero, E; 1999) (Cabrero, E; Gómez-Acebo, A; garcía-Alcazar, I; Carcía-Albacar, A; Luna, JD; Luna, A; 2000) 2001) 2001) (Cabrero, E; Luna, A; en prensa) (Comisiones Obreras, 1992) (Dubourg, C; Jegaden, D; Guillou, P; 1991) (Fanelli, C;Bertagnolio, GA;Deitinger, P;Macciocu, L;.…”
Section: Discussionunclassified